Quantification of amplitude modulation in wall-bounded turbulence - Dogan, Eda; Orlu, Ramis; Gatti, Davide; Vinuesa, Ricardo; Schlatter, Philipp (Fluid Dynamics Research, 2019)
Many recent investigations on the scale interactions in wall-bounded turbulent flows focus on describing so-called amplitude modulation, the phenomenon that deals with the influence of large scales in the outer region on the amplitude of the small-scale fluctuations in the near-wall region. The present study revisits this phenomenon regarding two aspects, namely the method for decomposing the scales and the quantification of the modulation. First, the paper presents a summary of the literature that has dealt with either or both aspects. Second, for decomposing the scales, different spectral filters (temporal, spatial or both) and empirical mode decomposition (EMD) are evaluated and compared. The common data set is a well-resolved large-eddy simulation that offers a wide range of Reynolds numbers spanning Re θ = 880-8200. The quantification of the amplitude modulation is discussed for the resulting scale components. Particular focus is given to evaluate the efficacy of the various filters to separate scales for the range of Reynolds numbers of interest. Different to previous studies, the different methods have been evaluated using the same data set, thereby allowing a fair comparison between the various approaches. It is observed that using a spectral filter in the spanwise direction is an effective approach to separate the small and large scales in the flow, even at comparably low Reynolds numbers, whereas filtering in time should be approached with caution in the low-to-moderate Re range. Additionally, using filters in both spanwise and time directions, which would separate both wide and long-living structures from the small and fast scales, gives a cleaner image for the small-scales although the contribution to the scales interaction from that filter implementation has been found negligible. Applying EMD to decompose the scales gives similar results to Fourier filters for the energy content of the scales and thereby for the quantification of the amplitude modulation using the decomposed scales. No direct advantage of EMD over classical Fourier filters could be seen. Potential issues regarding different decomposition methods and different definitions of the amplitude modulation are also discussed.
CRIS-Team Scopus Importer:2023-03-21
Keywords: amplitude modulation; scale interaction; turbulent boundary layer